DYNAMICS OF DAILY BLOOD PRESSURE RHYTHM AND HEART RATE VARIABILITY IN PATIENTS WITH ARTERIAL HYPERTENSION DURING A NEW FORM OF NIFEDIPINE (NIFECAD XL) TREATMENT - N. A. Mukhin; I. G. Fomina; V. A. Lyusov; L. V. Kozlovskaya; L. I. Zaitseva; E. M. Evsikov; A. E. Bragina; A. V. Vetluzhsky; V. V. Fomin (Российский кардиологический журнал)
Dynamics of daily blood pressure rhythm and heart rate variability in patients with arterial hypertension during a new form of nifedipine (Nifecad XL) treatment.